Effects of Pre-, Post- and Intra-Exercise Hyperbaric Oxygen Therapy on Performance and Recovery: A Systematic Review and Meta-Analysis - Huang, Xizhang; Wang, Ran; Zhang, Zheng; Wang, Gang; Gao, Binghong (Frontiers in Physiology, 2021)
Background: As a World Anti-doping Agency-approved treatment, hyperbaric oxygen (HBO2) therapy has been used to improve exercise performance in sports practice. Objective: We aimed to investigate the effect of pre-, post-, and intra-exercise HBO2 therapy on performance and recovery. Methods: A literature search was conducted using EMBASE, CENTRAL, PubMed, Web of Science, and SPORTDiscus to obtain literature published until May 2021. A total of 1712 studies that met the following criteria were identified: (1) enrolled healthy adults who were considered physically active; (2) evaluated HBO2 therapy; (3) included a control group exposed to normobaric normoxic (NN) conditions; (4) involved physical testing (isokinetic or dynamic strength exercise, maximal incremental treadmill/cycle exercise, etc.); and (5) included at least one exercise performance/recovery index as an outcome measure. The Cochrane risk of bias assessment tool was used to evaluate the included studies, and the heterogeneity of therapy effects was assessed using the I2 statistic by Review Manager 5.3. Results: Ten studies (166 participants) were included in the qualitative analysis, and six studies (69 participants) were included in the quantitative synthesis (meta-analysis). In comparisons between participants who underwent HBO2 therapy and NN conditions, the effects of pre-exercise HBO2 therapy on exercise performance were not statistically significant (P > 0.05), and the effects of post-exercise HBO2 therapy on recovery were not statistically significant either (P > 0.05). Although individual studies showed positive effects of intra-exercise HBO2 therapy on exercise performance, a meta-analysis could not be performed. Conclusion: Hyperbaric oxygen therapy before or after exercise had no significant effect on performance and recovery. However, hyperbaric oxygen therapy during exercise could improve muscle endurance performance, which needs to be confirmed by further empirical studies. At present, the practical relevance of these findings should be treated with caution.